Site-specific glycation of lens crystallins by ascorbic acid - Ortwerth, Beryl J.; Slight, Simon H.; Prabhakaram, Malladi; Sun, Yiping; Smith, Jean B. (Biochimica et biophysica acta, 1992)
The oxidation of ascorbic acid leads to the formation of several compounds which are capable of reacting with protein amino groups via a Maillard reaction. Radioactivity from [1- 14C]ascorbic acid was linearly incorporated into lens crystallins over a 10 day period in the presence of NaCNBH 3. This rate of incorporation was 6–7-fold more rapid than that obtained with [[ 14C]glucose under the same conditions. SDS-PAGE showed a linear incorporation into all the cyrstallin subunits. [1- 14]Ascorbic acid-label led α-crystallin was separated into into its component A and B subunits, and each was digested with chymotrypsin. HPLC peptide analysis showed a differential labelling of the various lysine residues. Analysis of the peptides by mass spectrometry allowed the identification of the sites and the extent of modification. These values ranged from 6% for Lys-78 to 36% for Lys-11 in the A subunit and from 5% for Lys-82 to an average of 38% for the peptide containing Lys-166, Lys-174 and Lys-175 in the B subunit. Amino acid analysis demonstrated a single modification reaction producing N ϵ -(carboxymethyl)lysine. This agreed with the mass increase of 58 observed for each modified peptide.